Preparation, Characterization, and Photocatalytic Property of Cu𝟐O-TiO𝟐 Nanocomposites - Longfeng Li; Maolin Zhang (International Journal of Photoenergy)
The Cu2O-TiO2 nanocomposites were successfully synthesized by the homogeneous hydrolysation, followed by the solvothermal crystallization and ethylene glycol-thermal reduction process, respectively. The obtained products were characterized by means of X-ray diffraction(XRD), Uv-vis diffuse reflectance spectroscopy, laser particle size analysis, and scanning electron microscopy (SEM), respectively. The photocatalytic performance of Cu2O-TiO2 nanocomposites was evaluated by the degradation of methyl orange (MO) as a model compound. The experimental results showed that the prepared Cu2O-TiO2 nanocomposite exhibited higher photocatalytic activity for the decomposition of MO than the pure Cu2O and the commercial Degussa P25 TiO2 under visible light irradiation.